Performance of Different Commercial Varieties of Sugarcane (Saccharum officinarum) for Yield and Quality Trait Influenced by Various Harvest Age Under Peninsular Zone of Maharashtra - Patil, A. S.; Pawar, G. R.; Mundhe, A. G.; Kadlag, A. D. (International Journal of Economic Plants, 2024)
A field experiment was carried out at Vasantdada Sugar Research Institute (VSI), Manjari, Pune, India during 2019–20, 2020–21 and 2021–22 crop seasons (36 months) to evaluate the performance of different harvesting periods of advanced varieties on yield and quality of sugarcane (Saccharum officinarum L.) under agro-climatic condition of peninsular zone of Maharashtra.Three harvesting dates i.e. H1-10 month, H2-12 month and H3-14 month and 10 different varieties including five early maturing sugarcane varieties V1-MS10001, V2-CoM 9057, V3-Co 09004 with two zonal check namely V4-CoC 671 and V5-VSI434 and five midlate maturing varieties V6-VSI08005, V7-CoVSI18121, V8-VSI12003 with two zonal check namely V9-CoM 0265 and V10-Co 86032 were evaluated in the split plot design with three replications. The varieties differed in stalk diameter and weight, and millable stalk number. Improvements in internodes number, stalk diameter and weight were increased with harvest age. Varieties produced better juice quality in canes harvested at 14 months. On the basis of pooled results obtained from three plant cane, it can be concluded that, Maximum cane yield (140.15 t ha-1) and CCS yield (19.33 t ha-1) can be secured by harvesting the sugarcane at 14 months after planting. With respect to varieties CoM 0265 recorded significantly higher cane yield (156.36 t ha-1) as well as CCS yield (18.81 t ha-1) which was followed by varieties VSI 08005 and CoVSI 18121. Whereas, significantly improved sucrose percentage was observed in VSI 434 (19.38%) which was harvested at 14 months after planting.